Analysis Study Perspective Learning: Gross Motor of Deaf Students at Extraordinary School - Juhanis; Sufitriyono (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study intends to determine the gross motor skills of deaf students at extraordinary schools using a survey method from a learning perspective. This is a quantitative descriptive study. This research was conducted at one of the schools in the city of Makassar, namely Public SLB 1 Makassar. The sample used in this study was 15 students using the Purposive Sample method. The data collection technique involved conducting a motor ability test, which included activities such as walking on a straight line for 5 meters, zigzag running for 15 meters, standing on one foot for 10 seconds, and jumping from a 15 cm block. The quantitative descriptive data analysis technique was employed. The results indicated that the gross motor skills of deaf children fell into the good category for 11 (73%), the sufficient category for 4 (27%), and the less category for 0 (0%). So it can be concluded that the gross motor skills of deaf students at Public SLB 1 Makassar are in the excellent category from a learning perspective, especially the PJOK subject.